Acute kidney injury: definition and epidemiology - Lopes,José António (2013)
Over the last decades, more than 35 different definitions have been used to describe acute kidney injury (AKI). Multiple definitions for AKI have obviously led to a great disparity in the reported incidence and mortality of AKI making it difficult or even impossible to compare the various published studies focusing on AKI. Therefore, it became crucial to establish a consensual and accurate definition of AKI that could desirably be used worldwide. Recent consensus criteria for AKI definition and classification [the Risk Injury Failure Loss of kidney function End-stage kidney disease (RIFLE) and the Acute Kidney Injury Network (AKIN) classifications] have led to more consistent estimates of its epidemiology. This review will present and critically discuss current literature about AKI diagnosis and epidemiology.